Improving Students' Writing Skills Through Media Wall Magazines in Indonesian Language Learning - Iswibowosari, Dian; Baharuddin , Hendra (Pustaka Digital Indonesia, 2023)
This study aims to increase learning achievement. Especially in Indonesian subjects. This is done because: (1) Indonesian academic achievement from year to year is unsatisfactory, (2) Many students are sleepy during Indonesian lessons, and (3) students are not very interested in Indonesian Language Lessons. This research uses a Classroom Action Research approach. (PTK) with a two-cycle system. The research subjects were fifth grade students at SD Negeri Tiron 01 Madiun Regency. Data collection techniques applied are tests and observations. Data analysis was carried out using a qualitative approach that focused on student achievement, student activity in learning, and learning implementation. The results of the study showed that the learning achievement of the Indonesian language students of class V at SD Negeri Tiron 01 Madiun Regency. Increasing the percentage of classical learning completeness from 83.3% (4 of 9 students) in Cycle I to 51.38% (7 of 9 students) in Cycle II. Student activity in learning also experienced an increase in the percentage of classical student activity from 50.00% (3 of 9 students) in Cycle I to 83.33% (6 of 9 students) in Cycle II. It can be concluded that using wall magazines can improve the learning achievement of fifth grade students. The findings in this study are wall magazines can provide inspiration for students to be able to express their ideas and creativity in written form. Through wall magazines, students can develop their writing potential so that they become better and better quality.